A Study on the Strengthening Performance of Concrete Beam by Fiber-Reinforced Polyurea (FRPU) Reinforcement - Jun-Hyuk Song; Eun-Taik Lee; Hee-Chang Eun (Advances in Civil Engineering)
Polyurea coating helps improve the ductility and toughness of structural members. A fiber-reinforced polyurea (FRPU) composite provides high load-carrying capacity and is applied by simply spraying it onto the member surface. Unlike existing reinforcement approaches, the FRPU coating method can prevent the ductility of concrete beams from deteriorating and the concrete surface from debonding. In this study, 20 concrete beams were tested with respect to their load-carrying capacity and flexural ductility using polyurea or FRPU reinforcement. The test variables included the type of reinforcing fibers, coating thickness, and weight-to-content ratio of the fibers in the FRPU. Moreover, the load-carrying capacity and mechanical behavior of all specimens were compared according to the content of the steel fibers, milled glass fibers, or carbon nanotubes (CNTs). Specimens reinforced using polyurea or FRPU were confirmed to retain the load-carrying capacity and flexural ductility to a certain degree after concrete failure at the tension face of the midspan section. The concrete beams ultimately failed through the fracture of polyurea or FRPU without debonding. Experiments were conducted to illustrate the strengthening effect by FRPU and determine its superiority.